NEW DITERPENOIDS FROM SALVIA-DIVARICATA - (:unkn) unknown (AMER SOC PHARMACOGNOSY, 1992)
Three new diterpenoids, 6-oxoroyleanone-18-oic acid [1], 6-oxo-12-methylroyleanone-18-oic acid [2), and horminone-18-oic acid [3], and a new linear sesquiterpene, salvinine [4], together with a group of known aromatic acids, were isolated from the aerial parts of Salvia divaricata.